A Syntactic Analysis of Noun Phrases in ‘Seasons’ by Wave to Earth - Marda Lena; Hapni Nurliana H.D Hasibuan; Alyza Putri; Aqila Fawwazah (Lingual: Journal of Language and Culture, 2025)
This research aims to examine the syntactic structure of noun phrases used in the song “Seasons” by Wave to Earth. The analysis found thirteen noun phrases divided into three main patterns, The identification of thirteen noun phrases in the lyrics is syntactically significant because it indicates that the song uses very minimal noun structure. The small number of noun phrases indicates that the songwriter does not rely heavily on complex noun phrase constructions. Instead, the lyrics prefer simple and straightforward patterns. Such as Determiner + Noun (Det + N), Quantifier + Noun (Quant + N), Quantifier + Determiner + Noun (Quant + Det + N), and singular Noun (N). The Det + N pattern is the most frequently occurring structure, followed by Quant + Det + N, one Quant + N and one singular noun phrase. Syntactically, these patterns demonstrate a simple writing style yet remain effective in conveying emotions and closeness of meaning. The results of this study indicate that the simplicity of the language structure in the song “Seasons” is an artistic strategy used to strengthen the emotional message and the life theme it wants to convey. Thus, a minimalist syntactic structure can be an effective aesthetic tool in building depth of meaning in musical works.